Analysis of Students’ Conceptual Understanding of Pythagorean Prerequisite Concepts - Retno Ayu Wulandari; Yelli Ramalisa; Duano Sapta Nusantara (Universitas Teknokrat Indonesia, 2026)
This study aims to determine students' ability to understand the prerequisite material for Pythagorean concepts. The study was conducted using a descriptive qualitative approach. The subjects of this study were students of class VIII B at SMP Adhyaksa 1 in Jambi City. Data collection involved written tests, interviews, and documentation, followed by analysis through data reduction, data presentation, and the formulation of conclusions. Data analysis was conducted based on concept comprehension indicators, namely 1) restating a concept, 2) writing down concepts in various mathematical representations, 3) using certain procedures, and 4) applying a concept. Based on the findings, of the 14 students, 7 were classified as having low comprehension, 5 were categorized at a moderate level, and 2 students achieved a high level of comprehension. This shows that students' conceptual understanding abilities vary. The results of the study show that students' conceptual understanding of the prerequisite material on Pythagoras tends to be low, with 50% in the low category. Some students showed fairly good achievement in the indicators of restating concepts and representing concepts. However, students were still weak in the indicators of selecting and using specific procedures and applying concepts.